Tregs levels and phenotype modifications during Amyotrophic Lateral Sclerosis course - Zucchi, Elisabetta; Banchelli, Federico; Simonini, Cecilia; De Biasi, Sara; Martinelli, Ilaria; Gianferrari, Giulia; Lo Tartaro, Domenico; Cossarizza, Andrea; D’Amico, Roberto; Mandrioli, Jessica (Frontiers in Immunology, 2025)
IntroductionT regulatory cells (Tregs) inversely correlate with disease progression in Amyotrophic Lateral Sclerosis (ALS) and fast-progressing ALS patients have been reported to exhibit dysfunctional, as well as reduced, levels of Tregs. This study aimed to evaluate the longitudinal changes in Tregs among ALS patients, considering potential clinical and biological modifiers of their percentages and concentrations. Additionally, we explored whether measures of ALS progression, such as the decline over time in the revised ALS Functional Rating Scale (ALSFRS-r) or forced vital capacity (FVC) correlated Treg levels and whether Treg phenotype varied during the course of ALS.MethodsTotal Tregs (detected by CD3, CD4, FoxP3, CD25, and CD127) were quantified at five time points over 54 weeks in 21 patients in the placebo arm of the RAP-ALS trial; next they were characterized for the expression of surface markers including CD38, CD39, CXCR3, and PD1. Repeated measures mixed models were used to analyze the longitudinal course of Tregs, considering potential associations with other clinical and laboratory characteristics. Correlations between ALSFRS-r or FVC and Tregs over time were similarly investigated.ResultsOur study showed that Treg levels did not change significantly on average during the observation period in our ALS cohort. However, PD1+Tregs decreased and CD39+Tregs increased over time. Male sex and cholesterol levels were associated with increasing Tregs (%) over time, while monocytes positively affected Treg concentrations. Treg concentrations showed a modesty association with FVC decline but were not associated with ALSFRS-r decline.DiscussionTreg levels remained stable during the ALS observation period and were not significantly associated with ALSFRS-r variations, suggesting that Treg numbers alone may have limited utility as a pharmaco-dynamic biomarker for ALS trials. However the observed changes in Treg phenotypes, such as the decrease in PD1+Tregs, indicate that phenotypic variations may warrant further investigation for their potential role in ALS progression and therapeutic targeting.